Biallelic CCM3 mutations cause a clonogenic survival advantage and endothelial cell stiffening. Issue 3 (13th December 2018) - Schwefel, Konrad; Spiegler, Stefanie; Ameling, Sabine; Much, Christiane D.; Pilz, Robin A.; Otto, Oliver; Völker, Uwe; Felbor, Ute; Rath, Matthias
Abstract: CCM3, originally described as PDCD10, regulates blood‐brain barrier integrity and vascular maturation in vivo. CCM3 loss‐of‐function variants predispose to cerebral cavernous malformations (CCM). Using CRISPR/Cas9 genome editing, we here present a model which mimics complete CCM3 inactivation in cavernous endothelial cells (ECs) of heterozygous mutation carriers. Notably, we established a viral‐ and plasmid‐free crRNA:tracrRNA:Cas9 ribonucleoprotein approach to introduce homozygous or compound heterozygous loss‐of‐function CCM3 variants into human ECs and studied the molecular and functional effects of long‐term CCM3 inactivation. Induction of apoptosis, sprouting, migration, network and spheroid formation were significantly impaired upon prolonged CCM3 deficiency. Real‐time deformability cytometry demonstrated that loss of CCM3 induces profound changes in cell morphology and mechanics: CCM3‐deficient ECs have an increased cell area and elastic modulus. Small RNA profiling disclosed that CCM3 modulates the expression of miRNAs that are associated with endothelial ageing. In conclusion, the use of CRISPR/Cas9 genome editing provides new insight into the consequences of long‐term CCM3 inactivation in human ECs and supports the hypothesis that clonal expansion of CCM3‐deficient dysfunctional ECs contributes to CCM formation.